The Prudence of Love: How Possessing the Virtue of Love Benefits the Lover - Silverman, Eric (Lexington Books, 2009)
The Prudence of Love: How Possessing the Virtue of Love Benefits the Lover focuses upon the intersection of philosophical, theological, and psychological issues concerning love. Eric Silverman advocates an account of the virtue of love derived from Thomas Aquinas's account of charity and makes three claims concerning love's effect on a person's happiness. First, he argues that there are at least five distinct ways that possessing the virtue of love contributes to the lover's happiness. Surprisingly, only one of these benefits is primarily relational, while the other benefits are largely psychological. Second, Silverman argues that the combination of love's benefits typically increases the lover's overall level of happiness. Finally, he argues that possessing a loving disposition is a more reliable strategy for increasing one's overall happiness than possessing an unloving disposition. Throughout The Prudence of Love, Silverman demonstrates that love's benefits are identifiable according to all four major views of happiness.